Aquaculture monitoring system using multi-layer perceptron neural network and adaptive neuro fuzzy inference system - Abu Hassan Abdullah; Sukhairi bin Sudin; Fathinul Syahir Ahmad Saad; Muhamad Khairul Ali Hassan; Muhammad Imran Ahmad; Kamarul Aizat bin Abdul Khalid (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The water quality is the most important parameter for aquatic species health and growth. The condition is very critical and is essential to monitor continuously. Poor water quality will affect health, growth and ability of the animal to survive. These also affected their harvesting yields based on the amount and size of the animal. The main water parameters such dissolved oxygen (DO), pH, temperature, salinity and turbidity are monitored and control for good water quality. The data were acquired by the developed instrument and send wirelessly through GPRS/GSM module to cloud-based database. The data were retrieved and the water quality is predicted using fuzzy logic and multi-layer perceptron. MATLAB software was used for the model which is developed based on Mamdani fuzzy interface system. The membership functions of fuzzy were generated, as well as the simulation and analysis of the water quality system. Results show that the performance of fuzzy method can improve system performance in monitoring the water quality. This system also provides alert signals to farmers based on specific limit value for the water quality parameters. This will help the breeders to make certain adjustment to ensure suitable water quality for the aquaculture system.